Quines relacions podrien existir entre l’escola i la comunitat? - Williams, Simon (kult-ur, 2021)
This research is written in the context of sociocultural theories of learning, where understanding is a relationship between people and their environment. The paper is an examination of how the researcher generated conditions which created connections between school and the local community in rural Thailand. The research experiments with the philosophy of Deleuze and Guattari and an encounter with contemporary art, to problematise existing thinking, build connections and new relationships with place. A qualitative approach is taken and the report is written in a narrative format, where critical events are analysed and discussed for their impact and value. Observation, sense and emotional data are used to inform the narrative.The research demonstrates the deterritorialising power of an art encounter as it slowed perception and created the need to invent new concepts. An assemblage of connections emerged resulting in rhizocurriculum that moved beyond the walls of the classroom towards new dialogues between school and community. The research found that the world of possibilities that art encounters point to are not easily manifested in practice and recommends continued experimentation with bodies that have the power to affect and be affected.